Tinjauan Faktor Air dan Sanitasi dengan Kejadian Stunting pada Balita - Mardiyatun Nasyidah; Nur Alam Fajar; Najmah Najmah (LPPM Hang Tuah Pekanbaru, 2022)
Globally, malnutrition manifests most frequently as a failure to achieve linear growth. Stunting occurs when a person's growth is restricted. Stunting is a major public health concern because it affects an estimated 165 million children younger than 5 years old, and the primary goal is to reduce stunting prevalence by 40% between 2010 and 2025. Stunting is linked to both water and environmental issues as well as nutritional ones. sanitation. The purpose of this literature review is to investigate the connection between the availability of clean water and the rate of stunting in children younger than five. Google Scholar, PlosOne, SpringerLink, the Wiley Online Library, and PubMed are just some of the electronic databases used in this literature review/narrative review/method of research.